Spatiotemporal analysis of land-use change and its impact on surface runoff in Tsushima Island, Japan - Tallar, Robby Yussac; Mauregar, Golan Geldoffer; Hirose, Eishi (Frontiers in Environmental Science, 2024)
Previous studies on watershed assessment have predominantly focused on general hydrological or technical results, rather than considering the spatiotemporal analysis of land use change and its impact on surface runoff. Motivated by this fact, the objective of this study is to conduct surface runoff analysis using GIS-based method due to land use change and to create a comprehensive mapping of potential flooding status for Tsushima Island, Japan as the selected study area. This study shows the interpretation results of satellite imagery by using spatiotemporal analysis embedded with a geographical information system (GIS)-based model approach to analyze rainfall data, topography or Digital Elevation Model (DEM), Moderate Resolution Imaging Spectroradiometer (MODIS) and Lansat 8 data by year 2024 until 2034. In conclusion, this study has provided an advanced approach to communicating information on potential flooding status to the public and related policymakers in the study area to mitigate efforts.Previous research on watershed assessments has primarily emphasized general hydrological or technical findings, neglecting the spatiotemporal analysis of land-use change and its influence on surface runoff. This study addresses this gap by employing a GIS-based method to analyze surface runoff variations due to land-use change on Tsushima Island, Japan. By leveraging spatiotemporal analysis within a GIS framework, the study interprets satellite imagery (Landsat 8 data, 2014(Landsat 8 data, -2024) ) to assess land use and watershed characteristics. This approach culminates in a comprehensive map depicting potential flooding risk across the island.